Stakeholder Perceptions of Socio-Ecological System Improvements: A Place-Based Study of Stream Habitat Enhancements - SMITH, Josh; KINDER Jr., Paul J; SELIN, Steven; HOFFMANN, Jamie (Journal of Environmental Management and Tourism; Vol 13 No 1 (2022): JEMT, Volume XIII, Issue 1(57), Spring 2022DO - 10.14505/jemt.v13.1(57).01, 2022)
Aquatic habitat enhancement projects typically occur in degraded socio-ecological systems. A major goal of these projects is to improve the ecosystem services that the streams provide to humans. In this work, we investigated how visitors at West Virginia’s Holly River State Park perceived the impact of an aquatic habitat enhancement project on ecosystem services provided by the Laurel Fork. The 172 surveyed visitors gave their current perceptions of the ecosystem services provided by the stream, as well as how they believed the ecosystem services would change upon completion of the aquatic habitat enhancement project. Results indicate that both anglers and non-anglers thought that the enhancement project would negatively impact the aesthetics and cultural ecosystem services provided by the stream. However, they felt that the provisioning ecosystem services, and recreation opportunities provided by the stream would improve. Our study highlights how important stakeholders’ perceptions are to habitat enhancement success.